The Application of Nanoparticles as Nanoadsorbents for Methylene Blue 2 Waste Using Zinc Oxide and Titanium Dioxide - Syarif, Febriansyah Husaini; Ratiani, Syifa Intan; Rizkita, Aden Dhana (Proceeding International Conference on Religion, Science and Education, 2024)
Nanoparticles are particles that have a size of ± 1 to 100 nm. There are various applications of nanoparticles, one of which is nanoadsorbent as used in wastewater treatment. One of the nanotechnology material products is zinc oxide (ZnO) nanoparticles which have the ability as a dye sensitized solar cell, catalytic converter, and catalytic activity so that it can be used as an adsorbent in environmental pollution treatment systems such as dichlorophenol-indophenol color degradation of heavy metal Pb (II) removal and methylene blue dye degradation. In the method used preparation, synthesis and test on methylene blue by means of photocatalyst and photodegradation, then on characterization using XRD, FTIR, SEM and DSC methods.